Function of sports and co-curricular activities on academic achievement in secondary schools students in ex-Fata Pakistan - Ashfaq, Muhammad (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
The study was designed to estimate the function of sports and co-curricular activities (CCA) on academic achievement among secondary schools students innewly merged districts in khyber Pakhtunkhwa Province ex Federally Administrative Tribal Areas (FATA). A sample size of 200 subjects was chosen from 10 high schools in the Frontier Region Kohat (FR Kohat). A questionnaire of five points likert scale after in quest of due authorization from heads of institutions was used to reach to the in facet of the recognizable truth. Arithmetical technique Mean, Percentage and Standard Deviation were run to inspect the collected records. The pollster analyze the link of sports and co-curricular contribution and its optimistic role to enhance educational performances of secondary schools students as to increase grade point average GPA. Sports and Co-curricular activities have optimistic outcome on students’ management. Those student who chip in in co-curricular activities show good performance. When learners execute these activities fruitfully and appropriately they are awarded for their first-class concert and manners and thus they take conceit on their achievement. Due to these achievement, they haul off additional, they gain improved self-confidence, poise and self-honor. Finally it was concluded that involvement in sports and co-curricular activities have an imperative result on students accomplishment score and other related activities. They achieve higher GPAs higher score in colleges admittance trial, better turnout, squat failure tariff and good physical condition performance. Furthermore schools are faced budget problems. Most of heads of institutions are not interested in sports and co-curricular activities. Most of teachers and parents consider these activities as wastage of time. Facilities are not available for students. Stuents play on their own risk because proper security are not available for partakers. Students need proper nutrition but unfortunately balance diet not available for them.